Comparative Analysis of the Sedative and Hypnotic Effects among Various Parts of Zizyphus spinosus Hu and Their Chemical Analysis - Baojian Li; Yuangui Yang; Zhongxing Song; Zhishu Tang (MDPI AG, 2024)
Zizyphus spinosus Hu (ZS), as a "medicinal and food-homologous" plant, has been used for a long history. The study was to assess the sedative and hypnotic effects among various parts of ZS. The model, diazepam (DZP), ZS kernel (ZSS), ZS flesh (ZSF), and ZS husk (ZSKS) group occurred subsequent to the successful establishment of the para-chlorophenylalanine induced insomnia model via intraperitoneal injection. The latency and duration of sleep in mice in each group were recorded. The substance basis of various parts of ZS was analyzed by the UPLC-QTOF-MS technique. The results showed that relative to the model group, DZP, ZSS, ZSF, and ZSKS groups demonstrated shortened sleep latency (p < 0.05) and extended sleep duration (p < 0.01). The GABA, 5-HT, and BDNF levels were significantly upregulated in the brain tissues of the mice in the DZP, ZSF, and ZSS groups (p < 0.01). However, the improvement in ZSKS was non-significant. Additionally, the mRNA and protein expression levels of 5-HT1AR, GABAARα1, and BDNF in mice in the DZP, ZSS, and ZSF groups were significantly enhanced (p < 0.01). However, the improvement in the ZSKS group was insignificant (p < 0.05). The examination of the substance composition across different parts revealed that the shared chemical basis contributing to the sedative and hypnotic potency of different parts of ZS may involve the presence of compounds such as (1) magnoflorine, (8) betulinic acid, (9) ceanothic acid, and (10) alphitolic acid. It provides a basis for further elucidation of the substance basis responsible for the functional and medicinal effects of ZS.